A study on the COVID-19 awareness affecting the consumer perceived benefits of online shopping in Vietnam - Kien Pham Van; Thu Ha Do Thi; Thu Hoai Ha Le (Cogent Business & Management, 2020)
The Covid-19 outbreak has turned out an opportunity for a recent noticeable increase in online shopping in Vietnam. Hence, this paper aims to discover how online shoppers react to their purchasing behaviour during Covid-19 time in terms of perceived benefits perspective. Based on the collected data from 427 Vietnamese online respondents during the social distancing period due to Covid-19, the research analyses the role of Covid-19 as a moderator variable in the relationship between benefits perception of the consumer and their online shopping activity. The result shows Covid-19 plays a moderating role in consumer's awareness of utilities, which encourages shoppers towards Online shopping. However, the affection of society could be a reason that consumers become more hesitant to shop online. In the meanwhile, awareness of the Covid-19 pandemic and marketing policies do not impact on online shopping significantly during the Covid-19 pandemic which is a conflict with previous researches. These findings can contribute to understanding consumer behaviour comprehensively, help companies deal with similar situation as well as recommendations for the government to support businesses effectively in the future.
Keywords: 650; consumer behaviour; online shopping; Covid-19; benefits perception